تربية الطفل البصلابة النفسية وعلاقتها بالتزان الانفعالي لدى التلاميذ المعاقين بصريا في مدينة حماة: البصلابة النفسية وعلاقتها بالتزان الانفعالي لدى التلاميذ المعاقين بصريا في مدينة حماة (Journal of Hama University, 2024)
This study aims at recognizing The Relationship between Psychological Rigidity and Emotional Stability for Visually Impaired Pupils at Assembly of Deaf and Blind in Hama City. The sample of study consists of 48 male/female visually impaired pupils at the Assembly of Deaf and Blind (fifth and sixth grades). The study used the descriptive analytic approach by using the scale of psychological rigidity prepared by Hammad Abdulladeif, and the scale of emotional stability prepared by Yasmeen Omar Halawa. Data have been analyzed by SPSS. The study confirms the following results for the visually impaired pupils of the sample:- The level of psychological rigidity is high.- The level of emotional stability is moderate.- There is a positive relationship between psychological rigidity and emotional stability.- There are statistically significant differences in average grades of psychological rigidity and emotional stability according to the cause of impairment (natal/acquisitus) for the sake of natal cases.